The summoning eaudiobook - Armstrong, Kelley (Darkest Powers, 2009)
My name is Chloe Saunders and my life will never be the same again. All I wanted was to make friends, meet boys, and keep on being ordinary. I don't even know what that means anymore. It all started on the day that I saw my first ghost-and the ghost saw me. Now there are ghosts everywhere and they won't leave me alone. To top it all off, I somehow got myself locked up in Lyle House, a "special home" for troubled teens. Yet the home isn't what it seems. Don't tell anyone, but I think there might be more to my housemates than meets the eye. The question is, whose side are they on? It's up to me to figure out the dangerous secrets behind Lyle House...?efore its skeletons come back to haunt me.